Factores medioambientales asociados a Infecciones Respiratorias en niños menores de 5 años que acuden al Hospital de Barranca - Alvarado Zuñiga, Carmen Rosa (2021)
Acute Respiratory Infections (IRAS) are the most common childhood illnesses. It is possible to contract them even without risk factors; although, if there are a greater number of factors, the higher the probability of becoming ill. Objective: To determine the environmental factors that are associated with Respiratory Infections in children under 5 years of age who attend the Barranca Hospital. Materials and methods: basic research, with a quantitative, descriptive, cross-sectional approach. The sample consisted of 120 children who attend the Barranca hospital and who belong to the jurisdiction of the Barranca province. The survey was used as a technique and as instruments a questionnaire on risk factors: environmental, social, individual. prior informed consent. Results: Children suffer from IRAS when: there is a lack of ventilation in the home (61.3%), when there are dusty areas near the home (54.5%), when exclusive breastfeeding of the child is inadequate (79.6 %), when there is no compliance with the vaccination schedule (62.9%) and when there is overcrowding at home (81.8%). Conclusions: The factors that influence acute respiratory infections in children under 5 years of age as environmental risk factors are poor ventilation and when there are dusty areas near the home, as individual risk factors when exclusive breastfeeding is inadequate and non-compliance of the vaccination schedule and as social risk factors are overcrowding at home.